Kesadaran Hukum Masyarakat Tentang Masa Iddah (Studi Kasus di Dusun Kemadang Desa Keteleng Kecamatan Blado Kabupaten Batang) - Mubarokah, Fatehatul (Al-Hukkam: Journal of Islamic Family Law, 2022)
The iddah period is a period of waiting for a woman after the breakup of her marriage with her husband, where a woman after separating from her husband is not allowed to marry, have contact with men who are not mahrom, spend the night outside the house where she lives and carry out ihdad. Legal awareness is self-awareness without pressure, coercion, or orders from outside to comply with applicable laws. The purpose of this study is to determine the legal awareness of the community regarding the iddah period and the factors that cause widows not to carry out the iddah period. This type of research is field research, using a qualitative approach, the data sources are primary and secondary. Primary data collection is done by observation technique. and secondary in the form of books, journals, theses and other libraries related to the law of the iddah period, obtained with documentation techniques. The data analysis used a qualitative analysis of the interactive model. This study resulted in findings that widows' legal awareness was still low, violations caused by their ignorance of the basis of sharia law governing the iddah period, while the factors causing violations of the iddah period were influenced by low economy, low level of education, lack of knowledge about Islamic law. and positive law and religious leaders who have less role in guiding the community in relation to the iddah period.